The Effect of Moringa Leaf Tea (Moringa oleifera) on Breast Milk Production in 0-6 Months Breastfeeding Mothers - Sa’idah, Silfia Nuzulus; Rahayu, Gita Gumilang (Oshada, 2025)
Moringa leaves contain various nutrients and phytochemical sources. Low micronutrients consumed by breastfeeding mothers will affect the ability to provide breast milk with sufficient micronutrient content for infant growth. The number of breastfeeding mothers in Indonesia has decreased significantly. According to WHO data, exclusive breastfeeding is globally 44% (2020), in Indonesia 67.96% (2022), West Java 80.08% (2023) and Bogor City 42.50% (2021). Therefore, WHO and UNICEF are trying to promote and support breastfeeding. Many factors cause low breastfeeding in infants, including lack of breast milk production. Moringa leaves are one of the herbal plants that contain steroids and phytosterols which play a role in increasing and facilitating breast milk production. To determine the effect of giving Moringa oleifera leaf tea on breast milk production in breastfeeding mothers aged 0-6 months at PMB E, Bogor City in 2024. This type of research is quantitative with a pre-experimental design with the One group pretest posttest design method. The number of samples in this study was 17 breastfeeding mothers aged 0-6 months at PMB E, Bogor City. The sampling technique used was accidental sampling. Data analysis using the Wilcoxon Signed Rank Test and obtained the average rank of breast milk production before and after the intervention, namely negative rank = 0, positive rank = 16 and ties = 1. Statistical tests obtained a Z value of -3.559 and an Asymp. Sig. (2-tailed) value = 0.000 <α 0.05. There is an effect of giving Moringa oleifera leaf tea on increasing breast milk production in breastfeeding mothers aged 0-6 months at PMB E, Bogor City in 2024.